Management Miller class III recession with tunnel subepithelial connective tissue graft - Kurnia, Shafira; Arief, Okkinardo (Opción, 2020)
The main objective of the work is to eliminate tooth hypersensitivity and etiologic factor of miller class III gingival recession and restore the gingival with tunnel subepithelial connective tissue graft and coronally repositioned flap. As a method, the treatment was done by scaling and occlusal adjustment first. One week after this treatment, the surgery was done for treatment of the gingival recession. As a result, the gingival recession was reduced from 2 mm to 0,5 mm and tooth hypersensitivity disappeared. In conclusion, subepithelial connective tissue graft and coronally repositioned flap is the appropriate technique for treat miller class III recession.